Cloud manufacturing as a sustainable process manufacturing route - Fisher, Oliver; Watson, Nicholas; Porcu, Laura; Bacon, Darren; Rigley, Martin; Gomes, R.L. (Elsevier, 2018)
Cloud Manufacturing (CM) is a service oriented business model to share manufacturing capabilities and resources on a cloud platform. Manufacturing is under pressure to achieve cost and environmental impact reductions, as manufacturing becomes more integrated and complex. Cloud manufacturing offers a solution, as it is capable of making intelligent decisions to provide the most sustainable and robust manufacturing route available. Although CM research has progressed, a consensus is still lacking on the concepts within CM as well as applications and scope beyond discrete manufacturing.